Heparin‐induced hyperkalemia, can LMWH cause hyperkalemia? A systematic review - Gedion Yilma Amdetsion; Aron Gudeta; Guy Lumley; Harkiran Sagoo; Ehab Aliledhin (eJHaem, 2023)
Abstract Hyperkalemia, an elevated blood potassium concentration exceeding 5.0 mEq/L, is associated with adverse outcomes and is frequently observed in hospitalized patients. Drug‐induced hyperkalemia accounts for a significant proportion of cases, with heparin, commonly used for venous thrombosis prevention, suspected to contribute, though less recognized than other heparin‐related side effects. Both unfractionated heparin (UFH) and low molecular weight heparin (LMWH) have been implicated in inducing hyperkalemia, primarily through the suppression of aldosterone levels and modulation of angiotensin II receptors. This systematic review examines the relationship between heparin, particularly LMWH, and hyperkalemia. Thirteen studies involving 1407 patients were analyzed. Findings indicated a lack of highquality evidence, with no significant increase in potassium levels associated with LMWH use. LMWH did not exhibit a dose‐response relationship with hyperkalemia incidence. Additionally, mechanisms underlying the hypothetical LMWHinduced hyperkalemia remained inconclusive. While this suggests that LMWH is unlikely to be a primary cause of hyperkalemia, caution is warranted, especially in patients with elevated baseline potassium levels.